Prediction of Innovation Capability: the Role of Mediation in the Relationship between Digital Transformation and Competitiveness with the PLS-SEM Model - Deri Firmansyah; Rahma Wahdiniwaty (International Journal of Management and Business Intelligence, 2023)
The importance of happiness management This study explores the mediating role of innovation capabilities (IC) on the relationship of digital transformation (DT) and competitiveness (CP), by proposing model construction. Four research questions and four hypotheses were posed. The survey method was carried out by distributing research instruments to 98 respondents, the collected data was used to analyze the relationship between digital transformation, innovation ability and competitiveness, also used to test hypotheses. Evaluation of predictions through structural equation models with partial least squares-structural equation modeling (PLS-SEM). Research findings show that digital transformation directly has a significant positive effect on competitiveness. Digital transformation directly has a significant positive effect on competitiveness. Digital transformation has a significant positive effect on innovation capabilities. The innovation capability has a significant positive influence on competitiveness. Innovation capabilities are proven to have a mediating effect on the influence of digital transformation on competitiveness.